The effects of commercial flower honey and turmeric on dermal wound in rats - Ithnin, Noor Idzatul Khairiah; Hashim, Kalthum; Mohd Yusoff, Md Sabri (2010)
Twenty healthy rats, ten adults (2-month-old) and ten young (1-month-old), were used in this study. Four skin biopsies were created at the dorsum of each rat under general anesthesia. The wound was each treated with honey, turmeric powder, turmeric-honey paste and a blank (control). The wounds were photographed on day 0, 1, 3, 5, 7 and 9. Wound area reduction was measured on day 9 after which the rats were euthanized. The skin samples were taken for histology. The results showed that there was no significant difference in the healing between treatments in young and adult rats. However, honey was the best treatment with the highest healing scores, followed by control, turmeric and honey-turmeric paste. Honey-turmeric paste resulted in a severe wound infection thus delayed healing.